2013
DOI: 10.1021/pr400212z
|View full text |Cite
|
Sign up to set email alerts
|

Extensive in vivo Human Milk Peptidomics Reveals Specific Proteolysis Yielding Protective Antimicrobial Peptides

Abstract: Milk is traditionally considered an ideal source of the basic elemental nutrients required by infants. More detailed examination is revealing that milk represents a more functional ensemble of components with benefits to both infants and mothers. A comprehensive peptidomics method was developed and used to analyze human milk yielding an extensive array of protein products present in the fluid. Over 300 milk peptides were identified originating from major and many minor protein components of milk. As expected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
166
4
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(190 citation statements)
references
References 57 publications
(100 reference statements)
15
166
4
5
Order By: Relevance
“…Except residues 51-59, the presence of these peptides in undigested HM has been observed previously (14,15). Two peptides of residues 1-18 and 1-23 are considered human counterparts of caseinophosphopeptides because they have the "acid motif " SerP-SerP-SerP-Glu-Glu, essential for the mineral-carrier potential (11).…”
Section: β-Cn-derived Bioactive Peptidesmentioning
confidence: 85%
See 3 more Smart Citations
“…Except residues 51-59, the presence of these peptides in undigested HM has been observed previously (14,15). Two peptides of residues 1-18 and 1-23 are considered human counterparts of caseinophosphopeptides because they have the "acid motif " SerP-SerP-SerP-Glu-Glu, essential for the mineral-carrier potential (11).…”
Section: β-Cn-derived Bioactive Peptidesmentioning
confidence: 85%
“…Other peptides were released after in vitro digestion and showed quite similar profiles in HM and pasteurized HM. Interestingly, there was no peptide identified which was released from residues 29-153, and Dallas et al also reported a similar observation (15). One possible explanation can be attributed to five glycosylation sites of OPN in human milk, all of which are located in residues 29-153 (36); glycosylated peptides are possibly released but lack of information regarding exact oligosaccharide structures makes them impossible to be identified by this peptidomic method.…”
Section: Opn-derived Peptidesmentioning
confidence: 95%
See 2 more Smart Citations
“…Only a few attempts have been reported to characterize the naturally occurring peptide content in human milk, but those have focused on the description of peptides produced from a small number of milk proteins (20,39). More recently, our group developed an analytical procedure to purify and analyze the endogenous peptide content in human milk (40).…”
mentioning
confidence: 99%